2022
DOI: 10.3390/jcm11185261
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Heparanase Activity and Endothelial Damage in COVID-19 Disease

Abstract: SARS-CoV-2 was first detected in 2019 in Wuhan, China. It has been found to be the most pathogenic virus among coronaviruses and is associated with endothelial damage resulting in respiratory failure. Determine whether heparanase and heparan sulfate fragments, biomarkers of endothelial function, can assist in the risk stratification and clinical management of critically ill COVID-19 patients admitted to the intensive care unit. We investigated 53 critically ill patients with severe COVID-19 admitted between Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…However, it is interesting that heparanase activity is significantly higher in Covid-19 versus non-Covid-19 patients. A recent work reported an average heparanase protein amount serum level of about 100 ng/mL in Covid-19 patients, with no differences between patients with different severities of ARDS 14. In contrast, here we observed that the serum heparanase protein amount is about 200 pg/mL in Covid-19 pneumonia patients.…”
contrasting
confidence: 86%
See 3 more Smart Citations
“…However, it is interesting that heparanase activity is significantly higher in Covid-19 versus non-Covid-19 patients. A recent work reported an average heparanase protein amount serum level of about 100 ng/mL in Covid-19 patients, with no differences between patients with different severities of ARDS 14. In contrast, here we observed that the serum heparanase protein amount is about 200 pg/mL in Covid-19 pneumonia patients.…”
contrasting
confidence: 86%
“…Previous studies have reported an increase in heparanase activity in Covid‐19 patients 13,14 as well as in several other systemic and pulmonary inflammatory conditions 15,16 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-five patients with positive SARS-CoV-2 PCR results and intensive care admission were included in this study. This patient population has been described in previous studies by our research group [24][25][26]. The serum samples of patients with COVID-19 infection in the second study population were collected between April 2020 and May 2021.…”
Section: Study Design/populationmentioning
confidence: 99%